Two models of ethical alignment through metacommunication in clinical situations. (28th September 2017) - Winther, Frederikke; Dindler, Camilla
Abstract : The literature on communication in patient-centred care typically focuses on physicians' alignment strategies. The goals of these strategies are diagnostic accuracy, effectiveness via compliance and patient-centredness. Although the success of these strategies can to some extent be measured, the ethical standards by which they are evaluated are not sufficiently clear. This article presents two models of alignment through 'explicit' metacommunication, derived from two different ethical perspectives on patient-centredness. The article first presents the concept of metacommunication and identifies two ethical perspectives that produce normative stands concerning patient-centredness: the logic of care and internal morality. Second, the article presents two models of how metacommunication can contribute to the visibility and accomplishment of these two ethical perspectives in clinical alignment.